Pengaruh Brand Image, Persepsi Harga dan Word Of Mouth Terhadap Keputusan Pembelian Konsumen The Highland Park Resort Hotel Bogor - Tjong Su Ling; Anton Widio Pratomo (Jurnal Ilmiah Pariwisata Kesatuan, 2020)
Competition is now increasingly fierce, making the company put orientation on customer satisfaction and satisfaction as the main goal. With more and more companies offering the same products and services to consumers, more and more alternatives are owned by consumers, so companies always try to meet the satisfaction of their customers. A good company image will make prospective customers more confident with the goods or services they will choose. The image will eventually become good, when consumers have enough memorable experience. WOM is a promotional activity that the level of control by marketers is very low but has an extraordinary impact on the company's products or services. WOM is able to spread so quickly if the individuals who spread it also have a wide network, news that is spread can be positive and negative news depending on what they feel when they enjoy the products or services offered. The purpose of this study is To find out and analyze the influence of Brand Image on Purchasing Decisions, To find out and analyze the effect of Price Perception on Purchasing Decisions, To find out and analyze the influence of Word of Mouth on Purchasing Decisions and To find out and analyze the effect of Brand Image, Price Perception, and Word of Mouth together on Purchasing Decisions. The number of respondents in this study amounted to 100 respondents taken from guests who have stayed at The Highland Park Resort Hotel Bogor. Research data were processed using SPSS. The results of this study are as follows: Brand Image has a positive and significant effect on purchasing decisions at The Highland Park Resort Hotel Bogor with a regression coefficient of 0.370 and a significant value of 0.017. Price perception has a positive and significant effect on Purchasing Decisions at The Highland Park Resort Hotel Bogor with a regression coefficient value of 0.312 and has a significant value of 0.001. Word of Mouth has a positive and significant effect on Purchasing Decisions at The Highland Park Resort Hotel Bogor with a regression coefficient of 0.576 and a significant value of 0,000. Brand Image, Price Perception, and Word of Mouth have a positive and significant effect on Purchasing Decisions at The Highland Park Resort Hotel Bogor with a calculated F value of 48.507 and greater than the F table of 2.70 and a significance value of 0,000 . Keywords: brand image, perceived price, WOM, Purchasing Decision